A qualitative exploratory study of user experience with a peer-support based, self-management website for people with a cardiovascular condition and diabetes - Chiung-Jung (Jo) Wu; Rohan Poulter; John J. Atherton; Richard J. MacIsaac; Tak Yan Leung; Patrick C. K. Hung; Mary-Anne Ramis (Digital Health)
Background Cardiovascular disease and Type 2 diabetes are two serious chronic health conditions that impact patients, families, and health services. Patients who experience both conditions can struggle to access relevant programmes to guide and educate them on successful self-management. Peer support has been proven to assist patients in managing these dual conditions, but the experience of using an online platform has not been previously explored. Aim To understand the experience of using a theory-based, peer-support, self-management website for people with cardiovascular and diabetes conditions in an Australian regional health service. Design An exploratory qualitative study was undertaken. Our study is reported according to COREQ guidelines. Methods Data were collected via online, semi-structured interviews approximately one week after participants were asked to engage with the website. Interviews were conducted to focus on the user experience, feasibility and usefulness of accessing the website, and how it helped support development of self-management skills. Interview data were transcribed from audio recordings into text files, thematic analysis was conducted for evolving themes. Results Fifteen participants agreed to be interviewed for the study. Findings revealed that participants found the website useful for providing relevant, comprehensive, and reliable online health information to help them manage their comorbidities. Participants appreciated the opportunity to share their experiences with others, and some expressed their interest in becoming peer supporters, to help others who might be trying to manage similar comorbidities. Conclusion Users’ experience of the peer-support, web-based programme was positive overall and supported the physical and emotional well-being of the participants, who were trying to manage two complex chronic health conditions. Considerations for further development are reported on.